2017
DOI: 10.18632/oncotarget.22228
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical PET imaging of glycoprotein non-metastatic melanoma B in triple negative breast cancer: feasibility of an antibody-based companion diagnostic agent

Abstract: High levels of expression of glycoprotein non-metastatic B (gpNMB) in triple negative breast cancer (TNBC) and its association with metastasis and recurrence make it an attractive target for therapy with the antibody drug conjugate, glembatumumab vedotin (CDX-011). This report describes the development of a companion PET-based diagnostic imaging agent using 89Zr-labeled glembatumumab ([89Zr]DFO-CR011) to potentially aid in the selection of patients most likely to respond to targeted treatment with CDX-011. [89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Moreover, this tracer has potential to visualize different levels of cell surface gpNMB expression on tumor cells. However, selective targeting of gpNMB in the tumor versus in normal organs could not be assessed in the animal study, since the CR011 antibody binds selectively to human gpNMB [ 30 ].…”
Section: Direct Targeting Of Tumor Cellsmentioning
confidence: 99%
“…Moreover, this tracer has potential to visualize different levels of cell surface gpNMB expression on tumor cells. However, selective targeting of gpNMB in the tumor versus in normal organs could not be assessed in the animal study, since the CR011 antibody binds selectively to human gpNMB [ 30 ].…”
Section: Direct Targeting Of Tumor Cellsmentioning
confidence: 99%
“…The discovery of ATL-836 antibody provides a promising platform for future diagnostics and therapeutics of TNBC as TF, otherwise known as platelet tissue factor/factor III, engages a crucial role in the signaling of cancer cells (apoptosis inhibition and cell migration promotion) and is found to be prominently presented on TNBC cells [ 106 , 107 ]. In 2017, another promising TNBC diagnostic imaging antibody agent targeting glycoprotein non-metastatic B (gpNMB)/osteoactivin was successfully developed in a TNBC xenograft animal model [ 108 ]. This discovery is crucial as gpNMB expression is significantly high in TNBC patients and, most importantly, in tumor progression reoccurrence [ 109 , 110 ].…”
Section: Future Diagnosismentioning
confidence: 99%
“…GPNMB is a type I transmembrane glycoprotein and expressed in the tumor stroma of 64% of human breast tumors and in the tumor epithelium of an additional 10% of tumors 45 . Recent studies 45,46 have identi ed high GPNMB expression in TNBC and suggested GPNMB as a potential biomarker for clinical research 47,48 . In this work, using QD520 (with emission maximum at 520 nm) and QD620 (with emission maximum at 620 nm) as uorescent nanocores, GPNMB-speci c QD520@cMIP and HER2-speci c QD620@cMIP were prepared by the proposed ROSIC method for targeting TNBC cells (GPNMB+) and HER2+ breast cancer cells, respectively.…”
Section: Fluorescence Imaging Of Triple-negative Breast Cancer Cellsmentioning
confidence: 99%